Effectiveness of Performance-Based Assessment Tools (PBATs) and the Students’ Academic Performance - et. al., Fahad Abdul Salendab, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Man tries to learn his surroundings by showing tendencies such as discovering, researching, asking questions, and noticing the relationships between objects. In other words, he tends to understand the world he lives in with various judgments. Therefore, it is important to raise individuals with advanced reasoning skills, mathematical thinking skills, proofing skills, problem solving skills, metacognitive knowledge, skills or qualifications. It can be said that this can only be possible with the right teaching models, methods, techniques and teachers who can use them in the most efficient way. In this context, the aim of the study is; To determine the difficulties in the preparation process for LGS, which has been implemented in our country since 2018, and the reflections of LGS on mathematics education applied in schools within the framework of the opinions of mathematics teachers and make suggestions accordingly. In the study, the screening model was adopted because it was tried to portray the thoughts of a certain group of participants on a subject. The sample of the study; It consists of 110 mathematics teachers who attended 8th grade classes in the 2018-2019 academic year. The data obtained from teachers' opinions were analyzed by content analysis method. According to this; The predominant opinion is that students have problems in understanding, interpreting, thinking and reasoning in the new examination system, however, because the textbooks and the exam are not parallel, teachers have various difficulties. In this direction, various activities can be organized to increase students' motivation and to gain reading habit. In addition, it is thought that it would be beneficial to provide teachers with in-service training for the The study aimed to assess the effectiveness of performance-based assessment tools (PBATs) at STI College Cotabato and their correlation with students' academic performance. The study employed a quantitative approach. This study surveyed two (2) groups of respondents. The first group consisted of teachers who taught Communication Arts 3 lessons, and the second group consisted of their students. Three (3) teachers served as teacher-respondents, and each teacher is responsible for thirty-five (35) students; therefore, a total of one hundred five (105) students were included in this study. The statistical tools used were the frequency, percentage count, mean, grand mean, and the Pearson Product-Moment Correlation Coefficient. Five (5) performance-based assessment tools were subjected to assessing their effectiveness to help students improve their target communication skills. The teachers assessed their use of the assessment tools to be very effective, while the students assessed their teachers’ use of the performance-based assessment tools as fairly effective. The students' performance in Communication Arts 3 subject was 85.97, described as satisfactory in the STI College Cotabato grading system. There was no relationship between the teachers' effectiveness of using the performance-based assessment tools and the students' academic performance. The effectiveness of the PBATs can only be achieved if they are used correctly and appropriately by the teachers. Furthermore, the various assessment tools for improving students' target skills were deemed valid and played an essential role in advancing students' skills. The recommendation of using the same tools in other areas of discipline is applicable since it was found to be effective. It further recommends that the institution design monitoring and implementing strategy relative to the effectiveness of performance-based assessment for the sustainability in developing students' communication skills. Lastly, studies exploring the feasibility of using the same tools in other areas of discipline to improve students' academic performance should be conducted.